A Quantitative Thrombin Time for Determining Levels of Hirudin and Hirulog™ - Reid, Thomas J, III; Alving, Barbara M (Thrombosis and Haemostasis, 1993)
The anticoagulant effect of recombinant hirudin (rHir) and HirulogTM has been monitored in patients with the activated partial thromboplastin time. Accurate monitoring with this test cannot be achieved if plasmas contain heparin, lupus anticoagulants, low concentrations of fibrinogen or other factors, or elevated fibrinogen-fibrin degradation products (FDP). We have therefore developed a simple, rapid, sensitive clot-based method, the quantitative thrombin time (QTT), to measure levels of rHir and HirulogTM in patient plasma (or whole blood). The QTT is performed by mixing a 1:10 dilution of patient plasma (50 μl) with human fibrinogen (50 μl, 128 mg/dl) at 37° C; the clotting time is initiated by adding human thrombin (50 μl, 5-7.5 U/ml). The concentration of HirulogTM or rHir in plasma can be determined by comparing the QTT in patient plasma with a Standard curve that is generated by adding different concentrations of anticoagulant to pooled normal plasma. Studies with whole blood using the same procedure yield similar results. In the absence of HirulogTM or rHir, the baseline QTT is the same in normal and abnormal plasmas (fibrinogen <150 mg/dl and FDP as high as 1024 μg/ml, elevated FDP alone, lupus anticoagulant, or heparin <0.9 U/ml). When known concentrations of either rHir or HirulogTM are added to abnormal plasmas, the mean observed concentrations as determined by the QTT deviate from the expected values by less than 10% (range 0-19%). The data indicate that the QTT is a simple, rapid, and accurate test for the determination of levels of rHir and HirulogTM in plasma or whole blood.